Voice Over for Home Security System - Ricky; Tanish M Sanghvi; Shivani Rajkumar; Tirishant Kartik; Dr. Sonia D’souza (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Smart Home Voice Control Hub is an advanced, integrated system design to seamlessly manage and operate a variety of smart home devices using voice commands. Recent years have witnessed significant advancements in home automation driven by wireless technologies. Among these, the IEEE 802.15.4 standard, RF, stands out for its low data rate, extended battery lif e, and secure networking capabilities. This article details a method for testing voice control implementation in smart homes, emphasizing compatibility with existing infrastructure. Utilizing low-power RF wireless modules and a microcontroller, the system caters to the needs of elderly and disabled individuals living independently. By focusing on voice recognition, it off ers enhanced security and control over household lighting and appliances. Experimental validation demonstrates the system's effectiveness in practical applications.
Keywords: AI based security; AI based home automation; Smart home; Wireless Technology; RF